(untitled) (REMUNOM, 2024)
Burns have a lasting and brutal impact on the quality of life of victims, especially in terms of body image, affect and skin sensitivity. Considering that burns are one of the greatest physical and psychological traumas that people can suffer, it is concluded that the rehabilitation (aesthetic and/or functional) of the patient is essential to maintain and improve the quality of life. It is necessary to analyze the quality of life of burn victims, not only in emergency care, but also in the follow-up of these patients. This is where the important role of the nursing team and their human care is revealed. This is where the extremely important role of nurses and their humanizing care comes into play. This is a qualitative research that used bibliographic review as an instrument to search for information. The search was carried out in the databases Scientific Electronic Library Online (SCIELO), PubMed, Periódicos CAPS and search engine sites through Scholar Google.Through the bibliographical research carried out, answers were established to the objective of the article, which is to know and analyze what the nurse’s actions should be in assisting patients with third-degree burns, aiming for a better quality of life and restoration of health.